(untitled) (Analysis in Theory and Applications, 2021)
Başar and Braha [1], introduced the sequence spaces _∞, c and c_0 of Euler-Cesáro bounded, convergent and null difference sequences and studied their some properties. Then, in [2], we introduced the sequence spaces [_∞]_e.r, [c]_e.r and [c_0]_e.r of Euler-Riesz bounded, convergent and null difference sequences by using the composition of the Euler mean E_1 and Riesz mean R_q with backward difference operator Δ. The main purpose of this study is to introduce the sequence space [_p]_e.r of Euler-Riesz p-absolutely convergent series, where 1 ≤ p